3D graphene/silver nanowire aerogel encapsulated phase change material with significantly enhanced thermal conductivity and excellent solar-thermal energy conversion capacity. Issue 14 (7th March 2022) - Lv, Linda; Wang, Yuqi; Ai, Hong; Chen, Taorui; Zhang, Xuan; Song, Shaokun
Abstract : A novel 3D graphene/silver nanowire aerogel encapsulated phase change material with significantly enhanced thermal conductivity and excellent solar-thermal energy conversion capacity was reported. Abstract : Scale-up applications of phase change materials (PCMs) are hindered by their solid–liquid leakage, low thermal conductivity, and poor solar-thermal conversion capacity. In this work, a novel reduced graphene oxide aerogel (rGAA) encapsulated PCM is reported by introducing a high aspect ratio of silver nanowires (AgNWs) to a reduced graphene oxide aerogel (rGA). The AgNWs pass through the pores of the aerogel and significantly improve the thermal conductivity of the lauric acid (LA) PCM. The obtained LA@rGA and LA@rGAA-2 show an ultrahigh latent heat of 185.8 J g −1 and 176.5 J g −1, respectively, which is 95.4% and 90.9% that of pure LA. In contrast to the penalty of a 4.5% decrease in the latent heat capacity, the thermal conductivity is significantly increased from 0.435 W m −1 K −1 for LA@rGA to 0.856 W m −1 K −1 for LA@rGAA-2, which is 1.63 and 3.21 times that of pure LA. The LA@rGAA-2 can effectively maintain a stable temperature by absorbing large amounts of latent heat from the surroundings during the heating process and dissipating the heat quickly to the environment during the cooling process. Furthermore, the novel LA@rGAA can realize an efficient solar-thermal conversion. Both LA@rGA and LA@rGAA display superhigh sunlight absorption capacities with average values exceeding 90% over the UV-Vis-NIR region, while the solar-thermal conversion efficiency is increased from 70.21% for LA@rGA to 94.54% for LA@rGAA-2. The significant enhancement in the solar-thermal conversion efficiency is ascribed to the successful construction of a 3D thermal conductive network by rGO and AgNW. Therefore, the novel LA@rGAA is believed to have significant potential in fields such as waste heat recovery, intelligent thermal management material for electronics, and solar energy utilization.